A Class of G-Semipreinvex Functions and Optimality - Xue Wen Liu; Ke Quan Zhao; Zhe Chen (Journal of Applied Mathematics)
A class of G-semipreinvex functions, which are some generalizations of the semipreinvex functions, and the G-convex functions, is introduced. Examples are given to show their relations among G-semipreinvex functions, semipreinvex functions and G-convex functions. Some characterizations of G-semipreinvex functions are also obtained, and some optimality results are given for a class of G-semipreinvex functions. Ours results improve and generalize some known results.